DEVELOPMENT AND VALIDATION OF A HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR DETERMINING METFORMIN HYDROCHLORIDE IN DRIED BLOOD SPOTS - Harahap, Yahdiana; Sari, Prastiwi Arum; Jatmika, Catur (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to develop an analytical method for determining metformin concentrations in human dried blood spots (DBS) using optimal chromatographic conditions and DBS preparation methods and validate the analytical methods. Methods: Analysis metformin HCl performed using C-18 columns (250 mm × 4.6 mm) at a column temperature of 40°C with a mobile phase acetonitrile phosphate buffer (40:60% v/v) at pH 7.0 using a flow rate of 0.8 mL/min, a photodiode array detector at a wavelength of 234 nm, and atorvastatin calcium as an internal standard. Samples were prepared by protein precipitation with 60% methanol and then drying using nitrogen gas at 60°C for 15 min before reconstituting in 200 μL of the mobile phase. Results: Invalidation procedures, the present methods met the acceptance criteria stated in the EMEA Bioanalytical Guideline 2011. The method was also linear at the concentration range of 25.0–5000.0 ng/mL (r=0.9997). Conclusion: The developed method for determination of metformin HCl in DBS sample was valid with a concentration range of 25.0–5000.0 ng/mL and can be applied to in vivo studies.